Examining linguistic ambiguity as a source of constructing funniness in English verbal jockes - Nguyễn, Hải Hà (University of Languages and International Studies, 2017)
M.A. Thesis. English Linguistics -- University of Languages and International Studies. Vietnam National University, Hanoi, 2011